The Troubled employee - Dartnell Corporation; Gerald T. Rogers Production (Chicago : Dartnell Corp., 1982)
Spells out some of the potential problems that some employees could be facing that interfere with their productivity, their attention span, and their very safety.
Keywords: Personnel management